Predictors of the Need for an Atrial Septal Defect Closure at Very Young Age - Tanghöj, Gustaf; Liuba, Petru; Sjöberg, Gunnar; Naumburg, Estelle (Frontiers in Cardiovascular Medicine, 2020)
An asymptomatic Atrial Septal Defect (ASD) is often closed at the age of three to five years using a transcatheter or surgical technique. Symptomatic ASD or ASD associated with pulmonary hypertension (PHT) may require earlier closure, particularly in combination with other noncardiac risk factors for PHT, but the indications for early closure and the potential risk for complications are largely unknown. The aim of this study was to assess risk factors for needing ASD closure during the first and second years of life. This case-control study included all children treated with surgical or percutaneous ASD closure between 2000-2014 at two out of three pediatric heart centers in Sweden. “Cases” were children with ASD closure at ≤ 1 or ≤ 2 years of age. Clinical data were retrieved from medical journals and national registries. Overall, 413 children were included. Of these, 131 (32%) were ≤ 2 years, and 50 (12%) were ≤ 1 year. Risk factors associated with an ≤ 2 years ASD closure were preterm birth, OR=2.4 (95% CI: 1.5-3.9); additional chromosomal abnormalities, OR=3.4 (95% CI: 1.8-6.5); pulmonary hypertension, OR=5.8 (95% CI: 2.6-12.6); and additional congenital heart defects, OR=2.6 (95% CI: 1.7-4.1). These risk associations remained after adjustments for confounding factors, such as need for neonatal respiratory support, neonatal pulmonary diseases, neonatal sepsis, additional congenital heart defects (CHD) and chromosomal abnormalities. ASD size:body weight ratio of 2.0, as well as a ratio of 0.8 (upper and lower limit of the ASD size:body weight ratios), was associated with increased risk of an early ASD closure. Risk factors such as very premature birth, very low birth weight, congenital and chromosomal abnormalities, neonatal pulmonary disease and need for ventilation support, as well as pulmonary hypertension, were associated with very early (<1 year of age) ASD closure. Several independent neonatal risk factors were associated with an increased risk of early ASD closure at two and at one year of age. An ASD size:body weight ratio is a poor predictor for indications for ASD closure.